CLINICAL APPLIENCE OF VEGETAL ORIGIN ANTIOXIDANTS - Yatsenko, L.D. (World of Medicine and Biology, 2014)
The article shows that free radicals and peroxides involve in carcinogenesis and blastomogenesis as mutagenes and carcinogenese promoters. Nontoxic antioxidants (natural and synthetic) are carcinogenesis-preventive and inhibiting agents. They inhibite metabolic activation ofcarcinogens, protooncogene activation, proliferation and mutagenic progression of transforming cells, theyr implantation, metastasis. Some natural antioxidants effective used in chemotherapy ofc-Micer (etoposide, teniposide, Vinca-alkaloids). Some other antioxidants (tea and grape flavonoids, phenols of propolis, selenium compounds, isodliocyanates, isoflavon genistein, terpenoids) are investigated as filture antitumor preparations. Antioxidants use as adjuvants vor tumor radiation and chemotherapy.